Penggunaan Media Pembelajaran Youtube untuk Meningkatkan Kemampuan Berfikir Kritis Siswa pada Mata Pelajaran Sejarah Kelas XI SMAN 1 Karangrejo - Lailatul Muthoharoh; Dita Hendriani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to determine the use of YouTube learning media in improving students' critical thinking skills in history subjects of class XI at SMAN 1 Karangrejo. The background of this study is based on the low interest in learning and students' critical thinking skills in understanding abstract and narrative historical materials. YouTube media is considered as one of the interactive and interesting learning alternatives, which can visualize historical events in a concrete and easy-to-understand manner. The formulation of the problem obtained by the author is how the use of YouTube media among class XI students at SMAN 1 Karangrejo, in supporting the teaching and learning process. How effective is the use of YouTube-based learning media on the critical thinking skills of class XI students, in history subjects at SMAN 1 Karangrejo. From the formulation of the problem, the purpose of writing is to find out the use of YouTube media among class XI students at SMAN 1 Karangrejo, in supporting the teaching and learning process. To find out the effectiveness of the use of YouTube-based learning media on the critical thinking skills of class XI students, in history subjects at SMAN 1 Karangrejo. This study uses a qualitative approach with a case study type. Data collection techniques are carried out through observation, in-depth interviews with history teachers and students, and documentation. The main focus of this study is on the learning process, student responses to the use of YouTube media, and how the media facilitates the development of students' critical thinking skills. The results of the study showed that the use of YouTube media had a positive impact on improving students' critical thinking skills. The historical videos shown were able to stimulate curiosity, encourage discussion, and help students analyze and evaluate historical events in more depth. In addition, students became more active, enthusiastic, and involved in the learning process.